2013
DOI: 10.1155/2013/265259
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in NAWM and NADGM in MS and CIS: Association with Candidate Biomarkers in Sera

Abstract: The aim of this study was to evaluate diffusion tensor imaging (DTI) indices in the corpus callosum and pyramidal tract in normal-appearing white matter (NAWM) and the caudate nucleus and thalamus in deep grey matter (NADGM) in all MS subtypes and clinically isolated syndrome (CIS). Furthermore, it was determined whether these metrics are associated with clinical measures and the serum levels of candidate immune biomarkers. Apparent diffusion coefficients (ADC) values were significantly higher than in controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…LA degree heavier, the FA values lower and a negative correlation ( Table 1, the LA grade shows in Figure 1A DTI can detect acute ischemic focal within 6 hours after ischemic cerebral stroke, even found MD lower at 105 minutes after ischemia attack. 8 significantly below these of LA lesions due to the decrease in total free-water molecules diffusion in ischemia area. In addition, FA values of LI infarcts were obviously higher than that of LA lesions, often prompts the anisotropy of the former more than the latter.…”
Section: A Dti Study Of Leukoaraiosis and The Differential Diagnosis mentioning
confidence: 87%
“…LA degree heavier, the FA values lower and a negative correlation ( Table 1, the LA grade shows in Figure 1A DTI can detect acute ischemic focal within 6 hours after ischemic cerebral stroke, even found MD lower at 105 minutes after ischemia attack. 8 significantly below these of LA lesions due to the decrease in total free-water molecules diffusion in ischemia area. In addition, FA values of LI infarcts were obviously higher than that of LA lesions, often prompts the anisotropy of the former more than the latter.…”
Section: A Dti Study Of Leukoaraiosis and The Differential Diagnosis mentioning
confidence: 87%
“…18 Consequently, MD measures appear to be more sensitive for detecting microstructural progressive changes at later MS disease stages compared with FA measures. 19 …”
Section: Discussionmentioning
confidence: 99%
“…In early MS, CST alterations have mainly been found in the internal capsule segments of the tract, whereas in chronic disease stages, periventricular CST has been investigated instead. 17 , 19 In general, within periventricular regions and the centrum semiovale, the FA values for the CST are lower as a result of fiber dispersion and the vicinity of the CST to gray matter or CSF. 17 By contrast, CST bundles reaching from the internal capsule to the brainstem (as investigated here) are quite densely packed (indicating a high degree of myelination and axonal density), resulting in high FA measures.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that macroscopic changes of CC had no direct association with cognitive dysfunction in such patients. [45] There were also some studies like study by Natarajan et al [46] in which they found that the most abnormal DTI indices were present in secondary progressive MS patients. According to a longitudinal cohort study in 2012 CC atrophy of 6 months could predict clinically definite MS within 2 years.…”
Section: As a Prognosis Indicatormentioning
confidence: 95%